PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN RISIKO PERUSAHAAN (STUDI EMPIRIS PADA LAPORAN TAHUNAN PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2011-2013) - SAIDAH, SITI (Jurnal Akuntansi AKUNESA, 2014)
This study aims to obtain empirical evidence about the effect of mechanism corporate governance on the non-financial corporate risk disclosure. Corporate governance variables as identified as managerial ownership, institutional domestic ownership, board size, the number of board meetings and the size of the audit committee. Purposive sampling method used in sample selection. There are 66 non-financial companies which are listed on the Indonesia Stock Exchange (IDX) period of 2011-2013 become the sample in this research.. The data analysis technique used in this study is hypothesis testing with multiple linear regression method.         The results of this study showed that the variable of domestic institutional ownership, board size and audit committee size effect on the corporate risk disclosure. In addition, variable managerial ownership and number of board meeting does not affect on the the corporate risk disclosure.   Keyword : Corporate governance, Risk Disclosure, Non Financial